A Study of Anomalous Wet and Dry Years in the Winter Precipitation of Pakistan and Potential Crop Yields Vulnerability - S. Sarfaraz ,; Tariq Masood Ali Khan, (Journal of Basic & Applied Sciences, 2015)
Pakistan experiences distinctively large rainfall variability on spatial as well as temporal scales. On spatial scale the rainfall variability is mainly caused by its peculiar topographic features encompassing from south to north of the country. On the other hand the temporal rainfall variability sometimes exceptionally large, does affect the climate of the country that in turn impacts the climate-dependent sectors like agriculture, hydroelectric power generation and ecology. In this study the 30-year winter season (December-March, DJFM) rainfall data of 35 meteorological sites of Pakistan have been analysed to identify the anomalous wet and dry years, their potential impact on crop yields across Pakistan and vulnerability of climate. The National Centre for Environmental Prediction (NCEP), US reanalysis data are used to investigate the association of the surface and upper air atmospheric circulation features responsible for anomalous wetness and dryness. This study may prove of some help for an improved winter rainfall prediction tool and better management of available water resources viz-a-viz optimal crop yields production.